(untitled) (Research, Society and Development, 2022)
One possibility of treatment in Aesthetics for folliculitis is a blue LED, as it acts on microbial control. Studies describe that the blue LED, with 405-470nm wavelength, has a bactericidal effect when irradiated in certain bacteria such as Staphylococcus aureus. This study aimed to evaluate the 450 nm blue LED’s efficacy as a modality in aesthetic treatments in the photoinactivation of the planktonic strains of S. aureus and S. epidermidis with power densities of 97, 110, 156, and 200 mW/cm2 in different energy densities. Bacterial suspensions of S. aureus (ATCC 25923) and S. epidermidis (ATCC 12228) were plated in 24-well plates and irradiated with other energy and power densities. After irradiation, each bacterial suspension was diluted in a phosphate buffer solution in a 96-well plate. Aliquots of 10 µL were collected from this dilution and streaked, in triplicate, in Brain Heart Infusion agar plates and incubated for 24h/37 °C. CFU counts were expressed in log10/mL and submitted to ANOVA and Tukey statistical tests. The energy and power densities used were insufficient to cause an antimicrobial effect on S. aureus or S. epidermidis planktonic cultures with a single light application.